A Rheumatic Fever Case Report Opereted Because of Acute Abdomen - Bektaş, Mehmet Selçuk; Üstyol, Lokman; Kaya, Avni; Temel, Hayrettin; Sal, Ertan; Üner, Abdurrahman (Fırat University, 2011)
Acute rheumatic fever is an autoimmune connective tissue disease involving multisystems. Following an upper respiratory streptococcal infection, the initial symptoms are fever, weakness and pale symptoms after a silent latent period of 10-14 days. Small joint involvement is rarely seen in acute rheumatic fever. A fourteen-year-old boy was referred to our hospital with complaints of pain and swelling on both his hands and ankles. The patient was underwent surgery for acute appendicitis at external medical center, with complaints of fever, abdominal pain and vomiting. To our patient the diagnosis was made according to modified Jones criteria including arthritis, carditis, elevated sedimentation rate, C-reactive protein, prolonged PR interval in electrocardiogram and high antistreptolysin O level. In conclusion, we should emphasize that acute rheumatic fever may also present with acute abdomen, in addition to the major symptoms and signs of disease. Later, large joint involvement and though rarely, small joint involvement can also be seen.

Akut romatizmal ateş bir çok sistemi tutan otoimmun bir bağ dokusu hastalığıdır. Streptokoksik bir üst solunum yolu enfeksiyonunu takiben 10-14 günlük sessiz bir devreden sonra ateş, halsizlik ve solukluk semptomları ile hastalık başlar. Akut romatizmal ateşte küçük eklem tutulumu nadirdir. Ondört yaşındaki erkek hasta her iki el ve ayak bileklerinde ağrı ve şişlik nedeniyle getirildi. Olgu dış merkezde ateş, karın ağrısı ve kusma şikayetleri ile akut apandisit ön tanısı ile opere edilmiş. Hastaya artrit, kardit, sedimantasyon ve C-reaktif protein yüksekliği, elektrokardiyogramda PR uzaması ve antistreptolisin O yüksekliği bulgularıyla modifiye Jones kriterlerine göre Akut romatizmal ateş tanısı kondu. Akut romatizmal ateşin akut batın tablosunda gelip majör bulgularının yanı sıra nadirde olsa küçük eklem tutulumuna olabileceğine dikkat edilmelidir.
Akut Batın Nedeniyle Opere Edilen Akut Romatizmal Ateş Olgusu